Effect of feeding goats with leguminous shrubs (Chamaecytisus proliferus ssp. Palmensis and Bituminaria bituminosa) on milk and cheese properties - S. Álvarez Ríos; P. Méndez; M. Fresno (Journal of Applied Animal Research, 2018)
Physical-chemical parameters, fatty acid profile and sensorial characteristics of experimental Palmero cheese from 2 equivalent groups of 20 Palmero goats fed 2 diets with different long fibre to concentrate ratio (65/35) or (35/65) with leguminous autochthonous forages (tagasaste and tedera) (DF) or wheat straw (DC) respectively as long fibre part of the ration were compared. A great influence on the milk basic composition from Palmero goats was observed when comparing dietary characteristics. Minimal effect on the fatty acid composition of the milk fat was observed but polyunsaturated fatty acids concentration was higher in DF milk. Cheeses were made on four consecutive days and were tested after 2, 15 and 60 days of ripening. Chemical composition was not significantly influenced by the diet while ripening affected all physicochemical parameters. Regarding fatty acids profile palmitic and linolenic acid concentration was higher in DC cheeses while DF cheeses presented higher linoleic values. The odour and aroma intensity was significantly higher for DF cheeses with the goat, butter and hay descriptors that can be correlated with a higher and better forage inclusion in the diet. DF cheeses were sweeter, with lower values for acidity and pungency stimulations and cause better appreciation by the expert panel.